Correction: Electrochemical promotion of catalysis over Pd nanoparticles for CO2 reduction. Issue 4 (24th February 2017) - Cai, Fan; Gao, Dunfeng; Zhou, Hu; Wang, Guoxiong; He, Ting; Gong, Huimin; Miao, Shu; Yang, Fan; Wang, Jianguo; Bao, Xinhe
Abstract : Correction for 'Electrochemical promotion of catalysis over Pd nanoparticles for CO2 reduction' by Fan Cai et al., Chem. Sci., 2017, DOI: 10.1039/c6sc04966d.